1999
DOI: 10.1063/1.123046
|View full text |Cite
|
Sign up to set email alerts
|

Molecular doping of gallium nitride

Abstract: Photoconductivity experiments were made on bulk GaN doped with Mg and O and grown using high pressures and high temperature. The bulk GaN:Mg,O was insulating, indicating compensation. The photoconductive response to photons above the energy band gap was comparable to that of epitaxially grown GaN:Mg samples. However, the UV-to-visible rejection ratio (solar blindness) was three orders of magnitude larger in the bulk GaN:Mg,O than for other epitaxially grown GaN samples. The dramatically improved visible reject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…For relatively low magnesium content (%0.1 Mg in Ga) we are able to obtain GaN samples characterized by a p-type conductivity and very good crystallographic properties. In these crystals the magnesium content is close to 10 20 cm ± ±3 [8]. However, if we increase the magnesium content up to 1% the obtained crystals are smaller and they show slightly different morphology.…”
Section: Crystal Growthmentioning
confidence: 64%
“…For relatively low magnesium content (%0.1 Mg in Ga) we are able to obtain GaN samples characterized by a p-type conductivity and very good crystallographic properties. In these crystals the magnesium content is close to 10 20 cm ± ±3 [8]. However, if we increase the magnesium content up to 1% the obtained crystals are smaller and they show slightly different morphology.…”
Section: Crystal Growthmentioning
confidence: 64%
“…The nominal distances between the cation and anion sites would, respectively, be 0.20 and 0.32 nm, so there would need to be significant relaxation if the simple dipole-dipole expression were to be valid and to give the observed value of D. Individually the magnesium and the oxygen are expected to act as acceptors ͑A͒ and donors (D), so that the complex could in principle form the state A ϩ ϪD Ϫ . It has been suggested by Tripathy et al 24 that such complexes can form near the GaN surface following treatment in KOH and molecular doping by MgO has been tentatively proposed by Pankove et al 25 Recent studies 23 of the electrical activity of GaN:Mg have also shown that oxygen donors and magnesium-containing complexes ͑which dissociate above 600°C) have a strong influence on the conductivity.…”
Section: A Interpretation As a Pair Spectrummentioning
confidence: 96%
“…2,3 Oxygen may also be important in co-doping with acceptors to increase the effective concentration in GaN. [17][18][19][20] There has been little work on understanding the role of oxygen during thermal processing of GaN. It is know that the temperature at which surface dissociation becomes significant during annealing of GaN is several hundred degrees lower in O 2 -containing ambients relative to pure N 2 ambients.…”
Section: ͓S0003-6951͑99͒00445-3͔mentioning
confidence: 99%